The Effect of Using Word Wall on The Eighth Grade Students' Vocabulary Achievement at SMPN 1 Jember in 2015/2016 Academic Year - Shallyntang Ditya Pradikasari; Zakiyah Tasnim; i Putu Sukmaantara (FKIP e-PROCEEDING, 2017)
Abstract: This experimental research was conducted to know whether or not there was a significant effect of using word wall on the eighth grade students' vocabulary achievement at SMPN 1 Jember in the 2015/2016 academic year. The research data were collected from the vocabulary pre-test and post-test. The deviation between the results of pre-test and post-test were analyzed statistically by using    t-test formula to know the mean difference between the experimental and the control groups. The value of t-test was 5.6850 that was higher than the value t-table at significant level of 5% with degree of freedom of 70, that was 1.994. It means that there was a significant difference between the experimental and the control group. In other words, there was a significant effect of using Word Wall on the eight grade students' vocabulary achievement at SMPN 1 Jember in the 2015/2016 academic year” was accepted. Hopefully, this research can help other researcher, teacher and students in English teaching and learning process. Keywords: vocabulary achievement, word wall, experimental research.